Pengendalian Intern Terhadap Sistem Pengawasan Produksi Dan Sistem Biaya (Studi Kasus PT. XYZ) - Julisar Julisar (Bina Nusantara University, 2010)
Business use internal control to guide their operations, safeguard assets and prevent abuses their system. Management is responsible for designing and applying five elements of internal control. The results from the evaluation of Internal Control in Production Control System and Cost System are the company has a good enough internal control in both their systems, such as, implement the segregation of duties, effective and efficiency in their manual operation procedure, controlling their documents and assets. But one thing the company needs to be done is the using of pre-numbered form. Most of all their forms have not been a pre-numbered form.